Cigarettes' use and capabilities-opportunities-motivation-for-behavior model: a multi-country survey of adolescents and young adults - Sabbagh, Heba Jafar; Abdelaziz, Wafaa; Quritum, Maryam; AlKhateeb, Nada AbuBakr; Abourdan, Joud; Qureshi, Nafeesa; Qureshi, Shabnum; Hamoud, Ahmed H. N.; Mahmoud, Nada; Odeh, Ruba; Al-Khanati, Nuraldeen Maher; Jaber, Rawiah; et al. (Frontiers in Public Health, 2022)
The use of cigarettes among adolescents and young adults (AYA) is an important issue. This study assessed the association between regular and electronic-cigarettes use among AYA and factors of the Capability-Motivation-Opportunity-for-Behavior-change (COM-B) model. A multi-country survey was conducted between August-2020 and January-2021, using the Global-Youth-Tobacco-Survey and Generalized-Anxiety-Disorder-7-item-scale. Multi-level logistic-regression-models were used. Use of regular and electronic-cigarettes were dependent variables. The explanatory variables were capability-factors (COVID-19 status, general anxiety), motivation-factors (attitude score) and opportunity-factors (country-level affordability scores, tobacco promotion-bans, and smoke free-zones) controlling for age and sex. Responses of 6,989-participants from 25-countries were used. Those who reported that they were infected with COVID-19 had significantly higher odds of electronic-cigarettes use (AOR=1.81, p=0.02). Normal or mild levels of general anxiety and negative attitudes towards smoking were associated with significantly lower odds of using regular-cigarettes (AOR=0.34, 0.52, and 0.75, p<0.001) and electronic-cigarettes (AOR=0.28, 0.45, and 0.78, p< 0.001). Higher affordability-score was associated with lower odds of using electronic-cigarettes (AOR=0.90, p=0.004). Country-level-smoking-control policies and regulations need to focus on reducing cigarette affordability. Capability, motivation and opportunity factors of the COM-B model were associated with using regular or electronic cigarettes.